Análise dos impactos sócio-ambientais da organização do espaço industrial de Cataguases - Oliveira Filho, Gerson Romero de (2009)
The city of Cataguases has excelled in the economy of Zona da Mata for being a pioneer in industry, whose logic of spatial organization displays two industrial patterns: the widespread and the concentrated. These two spatial arrangements unfold different socio-environmental impacts and, in what concerns taking actions, the two patterns are affected by the ineffectiveness of environmental surveillance. Also, the lack of planning is enhanced in both patterns, the widespread and the Distrito Industrial. As for the arrangement of objects and impacts resulting from industrial practice, it is observed the relevance of industry throughout the urban tissue, and in developing correlative economic activities to industrialization and urbanization. The singularity of each pattern reveals itself in the degree of pollution of the companies, in a much as the widespread pattern bears greater pollution potential. Lastly, spatial organization aspects of the companies portray significant differentiations regarding logistic of transport, size of the companies, site and position. In order to unveil such aspects, the analysis places the industrial development of Cataguases in different scales, as well as it asserts about the role of physical geography and the previously built space as conditioning factors to industrial activity and the environmental problems observed in the city